G. Jahukyan on the Concept of Grammatical Categories of the Verb - YUZBASHYAN, ANAHIT (Bulletin of Yerevan University B: Philology, 2021)
The article presents a new interpretation of the grammatical categories of the modern Armenian language, which gives academician G. Jahukyan in his monograph "Foundations of the theory of the modern Armenian language". His significant contribution to the solution of controversial issues related to the verbal system of modern Armenian language is evaluated. All verbal grammatical categories conjugation, time, person, number, gender, class, type, modality, their semantic content and methods of expressions in modern Armenian are clarified.
Keywords: G. Jahukyan, «Principals of Modern Armenian Theoretical Grammar», grammatical categories, conjugation, bases of the present, bases of the perfect, alternation and affixation